ANALISIS KOMPONEN KIMIA MINYAK ATSIRI PADA TANAMAN NILAM HASIL DISTILASI UAP AIR DENGAN MENGGUNAKAN KG-SM - Abdjul, Najmi; Paputungan, Mardjan; Duengo, Suleman (Sainstek, 2013)
Analysis of Chemical Components of Essential Oil Patchouli Plant, The Result In Steam Distillation Using The GC-MS. The aims of this study is to determine the chemical components of essential oils in patchouli plants. The method is steam distilation. Patchouli dried plant samples that have been chopped by 50 kg of steam distilled water to attract the patchouli oil components contained in the sample. The advantages of steam distillation is the hidrodifusition where moisture will get into the cell tissue of plant which resulting in rupture of the plant cell wall so that the oil contained in it will be pushed out. A mixture of water vapor and patchouli oil will flow to the condenser resulting in condensation and the resulting distilate. The distillate which containing oil and water separated by a separating funnel, until the patchouli oil. The oil which still contains water molecules that have been dried with MgSO4 previously prepared. The function addition of anhydrous MgSO4 is to bound water the which still contained in the oil. This isolation produced a yellow oil with a yield of 2,4%. The analysis of the chemical components of essensial oils is by using GC-MS. The results of using GC-MS analysis showed that there were 26 compound constituent of essential oils, with eight dominant peaks which are compounds: Patchouli alcohol (20,36%), Delta-guaiene (14,50%), Alpha-guaiene (12,89%), Pogostol (3,58%), Palustrol (1,64%), Beta-pinene (0,35%), Alpha-pinene (0,14%), and Alpha-patchoulena (7,54%). The main constituent of essential oil components are compound with patchouli alcohol levels obtained 20,36%.